Mycobacterium tuberculosis Rv0927c Inhibits NF-κB Pathway by Downregulating the Phosphorylation Level of IκBα and Enhances Mycobacterial Survival - Xia, Aihong; Li, Xin; Quan, Juanjuan; Chen, Xiang; Xu, Zhengzhong; Jiao, Xinan (Frontiers in Immunology, 2021)
Through long-term coevolution with its host, Mycobacterium tuberculosis (M. tuberculosis) uses multiple strategies to escape host defenses. The M. tuberculosis Rv0927c protein is predicted to be a short-chain dehydrogenase/reductase related to bacterial metabolism. However, the role of Rv0927c during M. tuberculosis infection remains unclear. Here, we observed that Rv0927c inhibited the expression of IL-6, TNF-α, and IL-1β, an effect dependent on NF-κB and p38 pathways. Western blot analysis of macrophages infected with recombinant Mycobacterium smegmatis strains showed that Rv0927c attenuated NF-κB activation by downregulating the phosphorylation of IκBα. Additionally, Rv0927c enhanced intracellular survival of M. smegmatis and pathological effects in mice. In conclusion, our findings demonstrate that Rv0927c functions as a regulator of inflammatory genes and enhances the survival of M. smegmatis.